Kontribusi Etika, Keberlanjutan dan Tanggung Jawab Sosial dalam Dunia Bisnis Internasional - Hendra Ibrahim; Rizky Azura; Enia Fadila Sitakar (Dharma Ekonomi, 2024)
This research aims to analyze the contribution of business ethics, sustainability, and corporate social responsibility (CSR) in international business. Using a descriptive qualitative method based on literature study, this research explores various literatures from scientific journals, academic books, and sustainability reports of global companies and organizations. The results show that business ethics play a role in building corporate reputation, maintaining stakeholder trust, and ensuring fair and transparent business practices. Sustainability is a key aspect of international business operations, especially in the face of global challenges such as climate change, resource exploitation, and social inequality. Meanwhile, the implementation of CSR in international business not only improves the company's image but also has a positive impact on society and the environment, in line with the Triple Bottom Line concept (people, planet, profit). In addition to the benefits, this study also identifies challenges in the implementation of business ethics, sustainability and CSR, such as regulatory differences between countries and the complexity of balancing economic and social interests. Therefore, companies are expected to integrate these principles into their business strategies to achieve long-term sustainability and meet the demands of a global market that increasingly emphasizes ethical and responsible business practices.